Accuracy of Predection Models in Determining Digested Protein and Total Digestible Nutrient on Local Ewes Ration containing Melinjo Peel - Iman Hernaman; Furi Siti Fauziyah Hasanah; Rida Septiana; Rendhy Ardiansyah; R. Bobby Adi Eryanto; Tidi Dhalika; Rahmat Hidayat; Ana R. Tarmidi (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2021)
The evaluation of digested protein and total digestible nutrient in rations containing melinjo peels could be done using several prediction models, but testing was needed to determine the level of accuracy. This study aimed to evaluate the accuracy of the prediction formula for protein digestibility and total digestible nutrient from rations containing melinjo peels of 5%, 10%, 15%, and 20%. Sixteen local ewes aged 11-12 monts with an initial body weight of 22.56 ± 1.46 kg were used to evaluate the value of digested protein and total digestible nutrient. The observational data were used to calculate the ratio of prediction to deviation value in assessing the accuracy of various prediction models for digested protein, namely Wardeh (1981) and Knight's and Harris (1966) models, while total digestible nutrient, namely Sutardi (2001), Wardeh (1981), and Harris et al. (1972) models. Wardeh (1981) and Knight and Harris’s (1966) digestible protein model, yielded ratio of prediction to deviation values of 3.28 and 3.37, respectively. Meanwhile, the ratio of prediction to deviation value on total digestible nutrient respectively from the highest value was Sutardi (2001), Wardeh (1981), and Harris et al. (1972) of 4.57, 3.68 and 1.91. In conclusion, Knight and Harris's (1966) digestible protein and Sutardi's (2001) total digestible nutrient model were the most accurate.